Perilaku Keluarga dalam Pengasuhan orang dengan Gangguan Jiwa di Kecamatan Kanigoro Kabupaten Blitar - Naura Nabina Fairuzahida (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
Family behavior of nurture mental disorders is the act of family who nurture mental disorders. The purpose of this study is to describe the behavior of family in nurture mental disorders in Kanigoro Blitar town which include medical treatment, fulfill activity daily living and psychosocial control mental disorders. The design uses a descriptive quantitative. The population in this study is family who has mental disorders amounting to 99. The sample is 33 family taken using purposive sampling tech- nique. Instrument in this study is using a questionnaire made by the researcher. Time data collection was done on February 2-28, 2016. The result showed that 49% family behavior of nurture is lack, 61% family behavior of medical treatment is lack, 64% family behavior of fulfill activity daily living is good and 46% family behavior of psychosocial control is good. Family behavior of nurture in particular medical treatment is lack cause of low economic and education factors. Recommendation to puskesmas Kanigoro is doing socialiszation medical treatment of mental disorders and doing early detection of mental disorders with making cadre of soul.